2004
DOI: 10.1086/425190
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Energetic Correlates of Divergent Selection for Basal Metabolic Rate in Laboratory Mice

Abstract: The aerobic capacity model postulates that high basal metabolic rates (BMR) associated with endothermy evolved as a correlated response to the selection on maximum, peak metabolic rate Vo2max. Furthermore, the model assumes that BMR and Vo2max are causally linked, and therefore, evolutionary changes in their levels cannot occur independently. To test this, we compared metabolic and anatomical correlates of selection for high and low body mass-corrected BMR in males of laboratory mice of F18 and F19 selected ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(184 citation statements)
references
References 44 publications
8
175
1
Order By: Relevance
“…Rather than operating directly on BMR, we argue that there is strong selection on organ systems that support levels of activity measured as sustained metabolic rates (Ksiazek et al, 2004) or as indexed by maximum metabolic performance in birds, measured by PMR C and PMR E . Recent insight into genes that regulate cell and organ growth through transcriptional regulation of protein and lipid synthesis may point to the specific targets for natural selection (Portsmann et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Rather than operating directly on BMR, we argue that there is strong selection on organ systems that support levels of activity measured as sustained metabolic rates (Ksiazek et al, 2004) or as indexed by maximum metabolic performance in birds, measured by PMR C and PMR E . Recent insight into genes that regulate cell and organ growth through transcriptional regulation of protein and lipid synthesis may point to the specific targets for natural selection (Portsmann et al, 2009).…”
Section: Discussionmentioning
confidence: 90%
“…Measuring the size/weight of the internal organs involved in the lactation process has been considered a simple, yet effective proxy for estimating the functional capacity of these organs in a range of species (Hurley, 2001;Karasov and McWilliams, 2005;Bauchinger et al, 2009). Our selection lines differ not only in their BMR but also in the mass of viscera essential for nutrient and energy turnover (intestines, liver, kidneys and heart); all are significantly heavier in non-reproducing H-BMR mice (Książek et al, 2004;Książek et al, 2009;Brzęk et al, 2007;Gębczyński and Konarzewski, 2009a). In this study, we showed that differences in organ masses are preserved after the first as well as the second reproductive bout, with H-BMR females having heavier viscera (particularly intestines and liver; Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The lowest oxygen concentration that did not change by more than 0.01% for at least 4 min was defined as BMR. No more than three individuals per family with the highest (H-BMR line) and lowest (L-BMR line) body-mass corrected BMR were chosen as progenitors for further selection and mated outside their families (for details, see Książek et al, 2004;Książek et al, 2009;Gębczyński and Konarzewski, 2009b).…”
Section: Animals and Their Maintenance During Experimentsmentioning
confidence: 99%
“…For example, is there a universal metabolic scaling law, why is resting metabolism correlated with daily energy use in mammals but not birds, how did the diverse resting and maximal metabolic rates of animals evolve and is there a necessary correlation between resting and maximal aerobic metabolism in vertebrates (Ricklefs et al, 1996;Clavijo-Baque and Bozinovic, 2012)? Some of these questions are very difficult to answer but ecological and evolutionary physiologists have recently made increasing use of artificial selection experiments to test hypotheses about the phenotypic and genetic integration of energy metabolism (Swallow et al, 1998;Koch and Britton, 2001;Ksiażek et al, 2004;Rezende et al, 2004;Sadowska et al, 2005Sadowska et al, , 2008Swallow et al, 2009;Wone et al, 2009;Gebczyński and Konarzewski 2009a, b,). One of the foci of these recent studies has been testing hypotheses about the evolution of endothermy.…”
Section: Introductionmentioning
confidence: 99%